A survey of grade school and high school libraries conducted by the Missionary Benedictine Sisters in the Philippines - Alcarez, M. Patricia; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1971)
Surveys twelve grade school and fourteen high school libraries conducted by the Missionary Benedictine Sisters in the Philippines for the school year 1969-1970. The study includes all aspects of the school library, such as the library collection, acquisition and organization of materials, use of library resources, library quarters and facilities, library administration, and library personnel. Findings on the status of the libraries are presented, analyzed and then compared against existing standards, here and abroad. In general, the libraries are found to be below the standards with which they are compared. Suggestions and recommendations to improve the conditions of these libraries are presented.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Benedictine nuns in the Philippines; High school libraries--Philippines.; School libraries (High school) See High school libraries